2015
DOI: 10.1175/bams-d-14-00105.1
|View full text |Cite
|
Sign up to set email alerts
|

JOYCE: Jülich Observatory for Cloud Evolution

Abstract: The Jülich Observatory for Cloud Evolution (JOYCE), located at Forschungszentrum Jülich in the most western part of Germany, is a recently established platform for cloud research. The main objective of JOYCE is to provide observations, which improve our understanding of the cloudy boundary layer in a midlatitude environment. Continuous and temporally highly resolved measurements that are specifically suited to characterize the diurnal cycle of water vapor, stability, and turbulence in the lower troposphere are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 59 publications
0
99
0
Order By: Relevance
“…It is permanently installed at FZJ. Amongst other instruments (see Löhnert et al, 2015), JOYCE contributed to HOPE with observations of a continuously scanning 35 GHz cloud radar, a Doppler lidar, and three microwave radiometers (one continuously scanning, one vertically pointing, and one continuously obtaining temperature profiles) for the spatiotemporal characterization of humidity and liquid water fields and for provision of the line-of-sightintegrated amount of water vapour and liquid water (Rose et al, 2005). The observations at the supersite Jülich were supported by high-resolved measurements of the vertical profile of the atmospheric temperature and water vapour mixing ratio, both at daytime and at night, which have been performed with the multi-wavelength polarization Raman lidar system BASIL of the Università degli Studi della Basilicata (UniBas), Italy (Di Girolamo et al, 2009, and the lidar system ARL-2 of the Max Planck Institute for Meteorology (MPIM) .…”
Section: Jülich Supersitementioning
confidence: 99%
See 1 more Smart Citation
“…It is permanently installed at FZJ. Amongst other instruments (see Löhnert et al, 2015), JOYCE contributed to HOPE with observations of a continuously scanning 35 GHz cloud radar, a Doppler lidar, and three microwave radiometers (one continuously scanning, one vertically pointing, and one continuously obtaining temperature profiles) for the spatiotemporal characterization of humidity and liquid water fields and for provision of the line-of-sightintegrated amount of water vapour and liquid water (Rose et al, 2005). The observations at the supersite Jülich were supported by high-resolved measurements of the vertical profile of the atmospheric temperature and water vapour mixing ratio, both at daytime and at night, which have been performed with the multi-wavelength polarization Raman lidar system BASIL of the Università degli Studi della Basilicata (UniBas), Italy (Di Girolamo et al, 2009, and the lidar system ARL-2 of the Max Planck Institute for Meteorology (MPIM) .…”
Section: Jülich Supersitementioning
confidence: 99%
“…As an example, a detailed depiction of IOP7 (25 April 2013) consisting of a turbulently driven boundary layer development topped with afternoon single cumulus clouds in the afternoon can be found in Löhnert et al (2015). There, it is demonstrated that a holistic view of the daily development of the boundary layer is only possible through the synergetic treatment of different ground-based remote sensors.…”
Section: Hope-jülichmentioning
confidence: 99%
“…A qualitative comparison of cloud water and cloud rain produced by the LES with the Cloudnet product (Illingworth et al, 2007) at the LACROS site complemented with the weather overview archive produced during HOPE is presented. Note that Cloudnet is a composite measurement product, which is derived from ceilometers, cloud radar, microwave radiometers and output from the COSMO model (e.g., Löhnert et al, 2015). Figure 4a shows the Cloudnet target classification at LACROS.…”
Section: Principal Character Of the Simulated Daysmentioning
confidence: 99%
“…At the permanent supersite JOYCE (Löhnert et al, 2014), measurements by the University of Basilicata Raman lidar system (BASIL) and an MWR were carried out, and auxiliary data from other instruments are available.…”
Section: Observations: Hopementioning
confidence: 99%